1984
DOI: 10.1042/bj2240667
|View full text |Cite
|
Sign up to set email alerts
|

Activities of glucokinase and hexokinase in mammalian and avian livers

Abstract: A radiochemical assay for glucokinase activity was developed for use in high-speed supernatants of liver. The maximum activities of glucokinase ranged from 0.4 to 3.8 mumol/min per g fresh wt. at 30 degrees C in some avian and mammalian livers, including pigeon, guinea pig and man, in which previous reports indicated zero activities. The reported maximum rates of hepatic glycogen synthesis in livers of rat and man in vivo are similar to the calculated glucokinase activities at 10mM-glucose; therefore glucokina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Despite the remarkable increase in net hepatic glucose uptake, however, the hepatic G-6-P concentration was not significantly increased at the end of the experimental period. One possibility is that flux through glucokinase (GK) was maximal in the control state, but because GK is not inhibited by G-6-P and is half-saturated at 10-15 mM (16,45), and because glucose uptake increased during hyperglycemia, this cannot be the case. Therefore, the discordance between hepatic glucose and G-6-P levels suggests that flux out of G-6-P increased proportionally to the rate of entry into the pool.…”
Section: Discussionmentioning
confidence: 90%
“…Despite the remarkable increase in net hepatic glucose uptake, however, the hepatic G-6-P concentration was not significantly increased at the end of the experimental period. One possibility is that flux through glucokinase (GK) was maximal in the control state, but because GK is not inhibited by G-6-P and is half-saturated at 10-15 mM (16,45), and because glucose uptake increased during hyperglycemia, this cannot be the case. Therefore, the discordance between hepatic glucose and G-6-P levels suggests that flux out of G-6-P increased proportionally to the rate of entry into the pool.…”
Section: Discussionmentioning
confidence: 90%
“…This contention is controversial; a number of groups have demonstrated that the activity of hepatic glucokinase is more than sufficient to support the rates of glycogen synthesis observed in vivo [13,32,33]. We consider that the low net glycogen synthesis from glucose in these systems is due, in large part, to an incomplete inhibition of glycogen degradation under these conditions.…”
Section: Resultsmentioning
confidence: 97%
“…The G6P effect was assessed by a radiometric assay using [ 14 C 1 ]mannose as a substrate as previously described [58] with slight modifications. The reaction medium used contained 75 mM Tris/HCl (pH 7.5), 7.5 mM MgCl 2 , 0.8 mM EDTA, 1.5 mM KCl, 2.5 mM ATP, 4 mM 2-mercaptoethanol, 0.1 % Triton X-100, 5 mM NaF, 5 mM NaN 3 and 2 mM [ 14 C 1 ]mannose ( 18.5 Bq/nmol; Amersham Pharmacia Biotech).…”
Section: Enzyme Activity Assaysmentioning
confidence: 99%